The Moderating Effect of Government Support between Gender Egalitarianism, Assertiveness, Future Orientation, and Female Leadership Effectiveness: Empirical Study of Public Universities in Saudi Arabia - Alajmi, Rajeh Hamad; Ahmad, Fais Bin; Al-Ansi, Ali Ali; Gorondutse, Abdullahi Hassan (International Review of Management and Marketing, 2017)
The underrepresentation of women in academic and administrative leadership roles is a global phenomenon. This study aimed to investigate the leadership effectiveness and the important factors that influence the women leadership effectiveness in the context of Saudi universities. There are still many obstacles face academic women leaders in universities. Among these obstacles, there is a limited authority of the women leaders, the centralization of decision making. Thus, this research investigates the impact of gender egalitarianism, assertiveness, and future orientation on the women leadership effectiveness in the public universities by taking government support as a moderating variable. A questionnaire survey was used to collect the data from 271 female academic leaders working in Saudi universities. The results found that gender egalitarianism, assertiveness, and future orientation have significant positive impact on leadership effectiveness. The value of this paper was in showing the significant of government support as a moderating variable for assertiveness, future orientation to enhance the women leadership effectiveness in Saudi universities. Keywords: leadership effectiveness, gender egalitarianism JEL Classifications: I23, J1